Is Beauty in the Hand of the Writer? Influences of Aesthetic Preferences through Script Directions, Cultural, and Neurological Factors: A Literature Review - Page, Alexander G.; McManus, Chris; González, Carmen P.; Chahboun, Sobh (Frontiers in Psychology, 2017)
Human experience surrounding the appreciation of beauty is not static. Many factors such as script direction and cultural differences directly impact whether, how and why we consider images beautiful. In an earlier study, Pérez González showed that nineteenth-century Iranian and Spanish professional photographers manifest lateral biases linked to reading writing direction (RWD) in their compositions. The present paper aims to provide a general review on this topic and intends to highlight the most relevant studies reporting preferences in the appreciation of beauty in individuals with different reading and writing directions and belonging to different cultural backgrounds.